PENGOLAHAN LIMBAH CAIR DENGAN LUMPUR AKTIF AEROBIK: STUDI KASUS INDUSTRI MINUMAN - Abdul Halim; Iqbal Kurniawan; Irliana Mai Sari; Wulan Dari Sapitri (Universitas Trisakti, 2022)
Problems with the aquatic environment can become a serious problem if it is linked to population growth and the manufacturing industry in Indonesia, which also means the increasing volume of wastewater originating from settlements and industrial areas. If not handled properly, wastewater problems can become a potential threat to the quality of a water and become a serious threat as a cause of water pollution. Nearly 60% - 70% of the air used will be wasted as wastewater which will generally enter water bodies without prior treatment efforts, thus contributing to pollution in water bodies. The purpose of this research is to evaluate alternative waste treatment conditions using activated sludge so that can determine the effectiveness of the method on decreasing test parameters such as COD, TSS, and pH stability. Data was collected using a lab-scale check that lasted 6 months with 4 research stages. The results showed the ability of aerobic bacteria in activated sludge to reduce the content of test parameters in liquid waste so that the end result follows the Industrial Liquid Waste Quality Standard according to applicable laws and regulations.